The Borrelia burgdorferi c-di-GMP Binding Receptors, PlzA and PlzB, Are Functionally Distinct - Kostick-Dunn, Jessica L.; Izac, Jerilyn R.; Freedman, John C.; Szkotnicki, Lee T.; Oliver, Lee D.; Marconi, Richard T. (Frontiers in Cellular and Infection Microbiology, 2018)
Cyclic-di-GMP (c-di-GMP) contributes to the regulation of processes required by the Lyme disease (LD) spirochetes to complete the tick-mammal enzootic cycle. Our understanding of the effector mechanisms of c-di-GMP in the Borrelia is evolving. While most LD spirochete isolates encode a single PilZ domain containing c-di-GMP receptor designated as PlzA, genome analyses have revealed that a subset encode a second PilZ domain protein (PlzB). The c-di-GMP binding potential of PlzB, and its role in LD spirochete biology, have not been investigated. To determine if PlzB binds c-di-GMP, plzB from B. burgdorferi isolate ZS7 was PCR amplified, cloned, and recombinant protein generated. PlzB bound c-di-GMP but not other nucleotides, indicating a specific binding interaction. To determine if PlzA and PlzB are functionally synonymous, a series of allelic-exchange gene deletion and cis-complemented strains were generated in the B. burgdorferi B31 background. B. burgdorferi B31-ΔplzA was competent to infect Ixodes scapularis larvae but not mice when delivered by either needle or tick feeding. B. burgdorferi B31-ΔplzA also displayed an atypical motility phenotype. Complementation in cis of B. burgdorferi B31-ΔplzA with plzA (B31-plzA KI) restored wild-type (wt) phenotype. However, a strain complemented in cis with plzB (B31-plzB KI) did not. The data presented here are consistent with an earlier study that demonstrated that PlzA plays an essential role in spirochete survival in the mammalian environment. We add to our understanding of the c-di-GMP regulatory network by demonstrating that while PlzB binds c-di-GMP, it is not functionally synonymous with PlzA. The absence of plzB from most strains suggests that it is not required for survival. One possibility is that cells that harbor both PlzA and PlzB might have enhanced biological fitness or increased virulence.